Perspektif Al-Quran Tentang Pembebasan Manusia Melalui Sarana Pendidikan Akhlak - Asma Yunita; Miftahul Jannah; Riska Rahmasari; Riski Rahmasari; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Muslims around the world, including Indonesia, have long faced colonialism (al-isti'mâriyyah). The significant deterioration of the lives of Muslims and long-term suffering in almost all spheres of life. Muslims will always be the monthly force of the infidels who dominate important sectors. One of the causes of moral decadence is the unstoppable entry of foreign cultures through social media and the lack of knowledge in filtering incoming cultures. The purpose of this study is to further explain the concepts of the Quran related to moral education, and to understand the concept of human liberation in the perspective of the Quran. This research model uses literature review techniques to examine several verses of the Quran related to the research topic. The results showed that efforts to improve the character and behavior of Muslims are by freeing mankind from ignorance, poverty, and neglect of Islamic moral values.